The Implementation of Character Education Values in Children of Female Worker Families in Langgudu District, Bima Regency - Nahrul Faidin; Tri Marhaeni Pudji Astuti; Sucihatiningsih Dian Wisika Prajanti; Puji Hardati; Nurlailatun Ramdani (International Conference on Science, Education, and Technology, 2023)
Character education is education that prioritizes instilling good behavioral values to children carried out by parents. This study aims to analyze the implementation of character education values carried out by the families of Female Workers in Langgudu District, Bima Regency. This research used a qualitative method with a phenomenological approach. The research was conducted in Langgudu Subdistrict, Bima Regency with a research focus on the implementation of children's character education values with indicators of discipline education, exemplary education, and advice education. Informant selection technique using purposive sampling technique. Data acquisition was carried out by means of interviews, observations and document studies. The results of this study indicate that the implementation of character education carried out by upper-class, middle-class and lower-class Female Worker Families in terms of exemplary aspects that parents still behave politely in front of children, parents always keep promises and parents get used to reading prayers before eating. Discipline education for children in upper-class families is very concerned, this is evidenced by parents' efforts to regulate and control children's activity time at all times, while in middle-class families, discipline education is not given much attention, then lower-class families, discipline education is not carried out due to the busyness of parents working outside the home. In upper-class families, the application of advice education is carried out strictly. However, it is different for middle-class families, by giving advice in a kind and gentle manner. Meanwhile, in lower-class families, advice education is not carried out regularly because parents are busier working outside the home.